Expression of genes for selected plant aminoacyl-tRNA synthetases in the abiotic stress - Baranašić, Jurica (Array, 2020)
Plants, as sessile organisms, have evolved intricate mechanisms to adapt to various environmental changes and challenges. Because various types of stress trigger significant decrease in global translation rates we examined the stress-related expression of aminoacyl-tRNA synthetases (aaRSs), enzymes that participate in the first step of protein biosynthesis. We have analyzed promoters of genes encoding cytosolic seryl-tRNA synthetase (SerRS), cytosolic aspartyl-tRNA synthetase (AspRS) and cytosolic cysteinyl-tRNA synthetase (CysRS) in Arabidopsis thaliana L., and examined SerRS, AspRS and CysRS gene expression in seedlings exposed to different abiotic stressors. Although global translation levels are repressed by stress, our results show that plant aaRSs expression is not decreased by osmotic, salt and heavy metal/cadmium stress. Moreover, during exposure to stress conditions we detected increased AspRS and CysRS transcript levels. SerRS gene expression did not change in stress conditions although participation of SerRS in stress response could be regulated at the protein level. Expression of the examined aaRS genes under stress correlated well with the length of their predicted promoters and the number of available binding sites for the stress related transcription factors. It thus appears that during stress it is important to keep steady state levels of aaRSs for translation of specific stress-related mRNAs and furthermore to rapidly continue with translation when stress conditions cease. Importantly, increased levels of plant aaRSs during stress may serve as a pool of aaRS proteins that can participate directly in stress responses through their noncanonical activities.